2018
DOI: 10.1063/1.5042121
|View full text |Cite
|
Sign up to set email alerts
|

A thermoacoustic imaging system with variable curvature and multi-dimensional detection adapted to breast tumor screening

Abstract: Microwave-induced thermoacoustic (TA) imaging is efficient in detecting anomalous absorption areas, especially breast tumors. The operation of previous imaging systems has generally suffered from complexity, and early-stage tumors could be missed because of signal loss. In this paper, we report a variable-curvature and multi-dimensional screening method realized by combining a redesigned adaptive algorithm and an integrated TA breast screening system (ITBCS) comprising a flexible detector and a traction device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…TAT combines the advantages of high microwave absorption contrast and high ultrasound resolution. To date, TAT has been used for breast cancer detection, foreign body detection, brain imaging, molecular imaging and blood imaging . TAT can directly recover the distribution of absorbed microwave energy density .…”
Section: Introductionmentioning
confidence: 99%
“…TAT combines the advantages of high microwave absorption contrast and high ultrasound resolution. To date, TAT has been used for breast cancer detection, foreign body detection, brain imaging, molecular imaging and blood imaging . TAT can directly recover the distribution of absorbed microwave energy density .…”
Section: Introductionmentioning
confidence: 99%
“…One potential caveat of this proposal is that in vivo tissue has heterogeneous distributions of permittivity and conductivity than that of the targets used in the present study, making it harder to compensate the electric field attenuation accurately. However, breast tissue is adipose‐dominated, and the conductivity contrast between malignant and normal breast tissues is up to sixfold at microwave frequencies . Thus, microwaves can easily penetrate several centimeters through normal breast tissue to reach deep tumors with acceptable distortions.…”
Section: Resultsmentioning
confidence: 99%
“…However, breast tissue is adipose-dominated, and the conductivity contrast between malignant and normal breast tissues is up to sixfold at microwave frequencies. 16 Thus, microwaves can easily penetrate several centimeters through normal breast tissue to reach deep tumors with acceptable distortions. Further evaluation of our compact handheld antenna utilizing both breast tumor-bearing animals and excised breast cancer specimens is under way in our laboratory, and the results from these studies will be reported in the near future.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations